Peranan Teori Belajar Psikoanalisa Dalam Pembentukan Karakter Remaja - Sustania Rahmawati; Arbaiyah Yusuf; Syaharani Zahra ‘Aisy K (Jurnal Ilmiah Wahana Pendidikan, 2023)
One of the theoretical approaches that studies mental processes involving structure, dynamics, as well as personality development is psychoanalysis. Psychoanalytic theory has a role in the formation of adolescent character through the application of psychological knowledge that analyzes the dynamics and psychological elements in influencing human behavior, as well as the importance of early life experiences in the formation of one's personality. This study uses a systematic literature review approach that is used to identify, study, and evaluate in a study. The literature review used comes from journals contained in Google Scholar and Sinta indexed journals, besides that research sources are also taken from several books and articles. This psychoanalytic theory plays a role in the interactions that adolescents carry out with their surroundings and the influence of the id, ego and superego in shaping the character of adolescents. According to this study, psychoanalysis aims to reveal how a person's personality develops and functions, where character formation is an important factor involved in this process. In its application, adolescents need to be given a positive environment from an early age because it can help and support positive growth and development as well. Besides that, the theory in this study also provides an understanding of the importance of self-reflection in adolescents.